Plasmonics: Manipulating Light at the Subwavelength Scale - Cheng-Ping Huang; Yong-Yuan Zhu (Active and Passive Electronic Components)
The coupling of light to collective oscillation of electrons on the metal surface allows the creation of surface plasmon-polariton wave. This surface wave is of central interest in the field of plasmonics. In this paper, we will present a brief review of this field, focusing on the plasmonic waveguide and plasmonic transmission. In the plasmonic waveguide, the light can be guided along the metal surface with subwavelength lateral dimensions, enabling the possibility of high-density integration of the optical elements. On the other hand, in the plasmonic transmission, the propagation of light through a metal surface can be tailored with the subwavelength holes, leading to the anomalous transmission behaviors which have received extensive investigations in recent years. In addition, as a supplement to plasmonics in the visible and near-infrared region, the study of THz plasmonics has also been discussed.